Changes in Sleep Duration During Transition to Statutory Retirement: A Longitudinal Cohort Study - Myllyntausta S; Salo P; Kronholm E; Aalto V; Kivimaki M; Vahtera J; Stenholm S (OXFORD UNIV PRESS INC, 2022)
Study Objectives: This study examined whether sleep duration changes during the transition from full-time work to statutory retirement and, if this were the case, which preretirement factors, including sociodemographic, work, lifestyle, and health factors, predict these changes.Methods: Data from repeated surveys of the Finnish Public Sector study, linked to records of retirement, were used. The study population consisted of 5785 participants who retired on a statutory basis in 2000-2011 and who had responded to surveys on sleep duration at least once immediately before and after their retirement (mean number of repeat study waves 3.6). Linear regression analyses with generalized estimating equations were used to examine changes in sleep duration around retirement.Results: Before retirement there was a slight decrease in sleep duration. During the 4-year retirement transition, sleep duration increased from 7 hours 0 minutes (95% confidence interval [CI] 6 hours 54 minutes to 7 hours 6 minutes) to 7 hours and 22 minutes (95% CI 7 hours 16 minutes to 7 hours 27 minutes); thus, mean increase being 22 minutes. Increase in sleep duration was greatest in those who were short sleepers, heavy drinkers, or had sleep difficulties. After the retirement transition, sleep duration remained at approximately the same level, as no significant changes were observed.Conclusions: This longitudinal study suggests that transition from full-time work to statutory retirement is associated with an increase in sleep duration.